Ultra-Clean Pure Shift 1 H-NMR applied to metabolomics profiling - Lopez, J.M.; Cabrera, R.; Maruenda, H. (Nature Publishing Group, 2019)
Even though Pure Shift NMR methods have conveniently been used in the assessment of crowded spectra, they are not commonly applied to the analysis of metabolomics data. This paper exploits the recently published SAPPHIRE-PSYCHE methodology in the context of plant metabolome. We compare single pulse, PSYCHE, and SAPPHIRE-PSYCHE spectra obtained from aqueous extracts of Physalis peruviana fruits. STOCSY analysis with simplified SAPPHIRE-PSYCHE spectra of six types of Cape gooseberry was carried out and the results attained compared with classical STOCSY data. PLS coefficients analysis combined with 1D-STOCSY was performed in an effort to simplify biomarker identification. Several of the most compromised proton NMR signals associated with critical constituents of the plant mixture, such as amino acids, organic acids, and sugars, were more cleanly depicted and their inter and intra correlation better reveled by the Pure Shift methods. The simplified data allowed the identification of glutamic acid, a metabolite not observed in previous studies of Cape gooseberry due to heavy overlap of its NMR signals. Overall, the results attained indicated that Ultra-Clean Pure Shift spectra increase the performance of metabolomics data analysis such as STOCSY and multivariate coefficients analysis, and therefore represent a feasible and convenient additional tool available to metabolomics.
Keywords: Metabolomics; Metabolome; Proton NMR; Metabolite; Chemometrics; Context (archaeology); Chemistry; Analytical Chemistry (journal); Chromatography; NMR spectra database; Spectral line; Biology; Organic chemistry; Biochemistry; Physics; https://purl.org/pe-repo/ocde/ford#1.03.00